2008
DOI: 10.1136/bjo.2007.125989
|View full text |Cite
|
Sign up to set email alerts
|

Does orally administered doxycycline reach the tear film?

Abstract: The inability to detect doxycycline in the tear film of patients undergoing treatment indicates that doxycycline does not directly inhibit MMP activity or the synthesis/secretion of these proteases and IL-1 from corneal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
2
24
0
1
Order By: Relevance
“…These effects are believed to occur at concentrations lower than those required for antimicrobial activity. For example, in a recent study, 36 oncedaily oral administration of 100 mg of doxycycline to humans did not produce detectable tear doxycycline concentrations but did reduce the tear matrix metalloproteinase-9 concentrations that are responsible for disease progression. Although antiprotease and antiinflammatory activity was not tested in that study, 36 multiple other studies 37,38 indicate that doxycycline, even at subantimicrobial concentrations, has important anti-inflammatory and anti-matrix metalloproteinase activity in people.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These effects are believed to occur at concentrations lower than those required for antimicrobial activity. For example, in a recent study, 36 oncedaily oral administration of 100 mg of doxycycline to humans did not produce detectable tear doxycycline concentrations but did reduce the tear matrix metalloproteinase-9 concentrations that are responsible for disease progression. Although antiprotease and antiinflammatory activity was not tested in that study, 36 multiple other studies 37,38 indicate that doxycycline, even at subantimicrobial concentrations, has important anti-inflammatory and anti-matrix metalloproteinase activity in people.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in a recent study, 36 oncedaily oral administration of 100 mg of doxycycline to humans did not produce detectable tear doxycycline concentrations but did reduce the tear matrix metalloproteinase-9 concentrations that are responsible for disease progression. Although antiprotease and antiinflammatory activity was not tested in that study, 36 multiple other studies 37,38 indicate that doxycycline, even at subantimicrobial concentrations, has important anti-inflammatory and anti-matrix metalloproteinase activity in people. Thus, it is likely that the doxycycline concentrations achieved in the tear film of northern elephant seals in the present study receiving 10 or 20 mg of doxycycline/kg would be expected to exert anti-inflammatory, antiprotease, or other nonmicrobial therapeutic activities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Doxycycline has both antibiotic and anti-inflammatory properties. The latter is due to the inhibition of matrix metalloproteinase and IL-1 activity [68] [69].…”
Section: ) For the Prevention Of Tear Evaporationmentioning
confidence: 99%
“…3 Smith et al 4 revealed that though oral DC does not reach tear film, it indirectly inhibits matrix metalloproteinases or the synthesis of these enzymes and interleukin-1 from corneal epithelial cells. Also Salminen 5 reported good penetrability of parenteral DC into the ocular compartments including cornea due to it's lipophilic nature.…”
mentioning
confidence: 99%